Enhancing Reproductive Health Comprehension in Elementary Students: An Educational Intervention in Sidamanik - Nurlela Petra Saragih; Almina Rospitaria Tarigan; Eka Isranil Laily; Rinawati Rinawati; Dewi Sartika Munthe; Ruth Sarah Julfrida Saragih; Lisbeth Laora Silitonga; Elfrida Nainggolan (International Journal of Community Service Implementation, 2025)
Reproductive health and sexuality education in elementary schools plays an important role in improving knowledge for students because there is still an opinion that it is a taboo when discussed in general. Reproductive health education can be provided when experiencing puberty and delivered with interactive education so that students understand about reproductive health. Activities are carried out face-to-face with educational methods with lecture, question and answer and discussion techniques. The results of the activity are an increase in the knowledge of elementary school teachers and students about adolescent reproductive health. Thus, efforts to disseminate information about reproductive health for elementary school teachers and students are needed and are expected to be carried out on an ongoing basis. The method used in this community service activity is by conducting educational activities, followed by discussions and questions and answers. After conducting this community service activity, students, teachers are happy and students understand the definition, benefits, types of reproductive organs and how to keep them clean and healthy